Fire in the Amazon: impacts of fuel loads and frequency on ants and their interactions with seeds - Paolucci, Lucas Navarro (2016)
Fire is a major disturbance shaping the distribution and diversity of species across several biomes. Tropical forests rarely burn naturally, but human activities such as logging and agriculture fragment the original habitat, increasing fuel loads and consequently the flammability and frequency of understory fires. Southern Amazonian forests are currently facing extremely land-use change, and are under a state of high recurrent burning. Understory fires severely degrade the structure of these forests, but the role of fuel loads or fire frequency on their faunal communities has been little studied. Here we experimentally addressed how understory fires affect shade-adapted ant communities from southern Amazonian forests. In the first chapter we investigated the influence of fire and fuel loads on ant communities and their interactions with myrmecochorous seeds. Single fires and fuel addition were applied to plots in six replicated blocks, and ants were sampled in four strata: subterranean, litter, epigaeic and arboreal. We found that highly specialized taxa are the most sensitive, but species composition remained little altered. Fire reduced rates of seed location and transport, which we attribute to increased thermal stress, although enhanced fuel loads will not decrease ant diversity and ecosystem services through increased fire severity. In the second chapter we investigated the role of recurrent fires on ant communities, and assessed the extent to which their responses are consistent with those of trees. Two plots were subjected to annual and triennial fires over a six-year period, while one plot remained unburnt. Species diversity and composition varied similarly for trees and ants, with minor effects on richness, increased evenness and different species composition due to fire. However, fire had a much more severe impact on abundance and biomass of trees than of ants, reflecting the direct effects of fire on the former and indirect on the latter. In conclusion, we suggest that the prevention of recurrent fires should be of special concern for the maintenance of biodiversity of these forests, particularly considering that ants have a well-established role on indicating disturbances on other faunal groups, so such negative effects likely occur for other taxa from these forests as well.